Simulium (Nevermannia) khunklangense, a new species of black fly (Diptera: Simuliidae) from Chiang Mai, Thailand - Hiroyuki Takaoka (2018)
Simulium (Nevermannia) khunklangense sp. nov. is described from females, males, pupae and larvae collected in Doi Inthanon National Park, Chiang Mai, Thailand. This new species is placed in the vernum species-group of the subgenus Nevermannia and is similar to S. (N.) chomthongense Takaoka and Srisuka described from Doi Inthanon National Park, Thailand, but is distinguished in the male by the number of enlarged upper-eye facets and the relative width of the hind basitarsus against the hind tibia and femur, and in the pupa by the short common basal stalk of the gill and the cocoon with an anterodorsal bulge or a short anterodorsal projection. Taxonomic notes are provided to separate this new species from five other known species of the vernum species-group, which share an accessory sclerite on the larval abdomen, a rare characteristics in this species-group. Copyright © 2013 Magnolia Press.